Kualitas Audit sebagai Pemoderasi: Pengaruh Pengungkapan ESG terhadap Kinerja Keuangan Perusahaan Migas di ASEAN - Zatalini Ulvy; Eva Herianti (Owner : Riset dan Jurnal Akuntansi, 2026)
This study examines the impact of ESG disclosures on the financial performance of ASEAN oil and gas companies, with audit quality as a moderating variable, using 130 firm-year observations from ASEAN Xchange-listed firms during 2020–2024 and panel data regression. Addressing the limited empirical evidence on the moderating role of audit quality in the ESG–financial performance relationship within environmentally sensitive industries in emerging ASEAN markets, this study fills an important research gap. The results show that environmental disclosure has a significant negative effect on ROE due to short-term cost burdens, while social and governance disclosures exhibit positive but insignificant effects. Audit quality, measured by multidimensional measurement, using Big4 affiliation, auditor tenure, and auditor opinion, positively moderates the relationship between environmental disclosure and financial performance, but shows no moderating effect for social or governance disclosures. Theoretically, this study contributes to legitimacy and stakeholder theory by demonstrating that the financial consequences of ESG disclosure depend on both disclosure content and the credibility of corporate reporting mechanisms. Practically, the findings suggest that ASEAN oil and gas companies should manage ESG disclosures strategically to avoid short-term cost burdens, while high audit quality enhances credibility, strengthens market trust, especially for environmental disclosures, and can support financing access and long-term financial performance.